Study of novel coating strategy for coronary stents: simutaneous coating of VEGF and anti- CD34 antibody - Song,Chun-Li (2015)
AbstractIntroduction:Intravascular coronary stenting has been used in the treatment of coronary artery disease (CAD), with a major limitation of in-stent restenosis (ISR). The 316 stainless steel has been widely used for coronary stents. In this study, we developed a novel coating method to reduce ISR by simultaneously coating vascular endothelial growth factor (VEGF) and anti-CD34 antibody on 316L stainless steel.Methods:Round 316L stainless steel sheets in the D-H group were polymerized with compounds generated from condensation reaction of dopamine and heparin using N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide (EDC) and N-hydroxysuccinimide (NHS). Sixteen sheets from the D-H group were further immersed into 1ug/ml VEGF165 and 3mg/ml heparin sodium one after another for 10 times, and named as the D-(H-V)10 group. Eight sheets from the D-(H-V)10 group were coated with anti-CD34 antibody and termed as the D-(H-V)10-A group. Immunofluorescence assay and ELISA were used to evaluate whether the 316L stainless steel disks were successfully coated with VEGF and anti-CD34 antibody.Results:The results of immunofluorescence assay and ELISA showed that VEGF could be detected in the D-(H-V)10 and D-(H-V)10-A group, suggesting the steel sheets were successfully covered with VEGF. Anti-CD34 antibody could only be observed in the D-(H-V)10-A group, which was the only group coated with CD34 antibody. Both results suggested that the 316L stainless steel sheets were successfully coated with VEGF and anti-CD34 antibody.Conclusion:Our study developed a method to simultaneously coat VEGF and anti-CD34 antibody to stainless metal steel. This research serves as a fundamental role for a novel coating strategy.